2013
DOI: 10.1097/aud.0b013e31826d0ba4
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Listening Effort for Various Types of Masker Noises

Abstract: It is well established that older listeners have more difficulty understanding speech in background noise than younger listeners (e.g. Dubno et. al., 1984). Some have attributed this increased difficulty to peripheral hearing loss, while others suggest that older listeners may perceive listening in noise as difficult and effortful because it requires them to exert more cognitive resources . The purpose of the present study was to directly evaluate the relationship between cognitive function, listening effort a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
172
5
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(208 citation statements)
references
References 93 publications
18
172
5
5
Order By: Relevance
“…It is difficult to know if and to what extent variations along these dimensions affect the relationship to cognition, and whether these variations may explain, at least in part, inconsistencies between studies. For instance, could differences in target speech help explain why some studies (Desjardins and Doherty 2013;Moradi et al 2014), using a complex sentence perception test, found a significant correlation between reading span and intelligibility, while another study (Kempe et al 2012), using syllables and the same cognitive test, did not? The goal of this study is to systematically vary the complexity of the listening situation and to investigate how this variation affects the relationship between intelligibility and assorted cognitive measures.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to know if and to what extent variations along these dimensions affect the relationship to cognition, and whether these variations may explain, at least in part, inconsistencies between studies. For instance, could differences in target speech help explain why some studies (Desjardins and Doherty 2013;Moradi et al 2014), using a complex sentence perception test, found a significant correlation between reading span and intelligibility, while another study (Kempe et al 2012), using syllables and the same cognitive test, did not? The goal of this study is to systematically vary the complexity of the listening situation and to investigate how this variation affects the relationship between intelligibility and assorted cognitive measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of a structured interview or self-report questionnaire would have added information, for example, as to whether the perceived impact of HI in daily life is related to cognitive function (Ng, Rudner, Lunner, & Rönnberg, 2013). This question has so far received relatively little attention but is motivated in view of the connection between speech recognition in adverse conditions, cognitive capacity and listening effort (Desjardins & Doherty, 2013;Rudner et al, 2012). Effort in hearing has in turn been identified as a risk factor for stress-related sick-leave in individuals with HI (Kramer et al, 2006).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Bayliss et al, 2005;Kane et al, 2005;Unsworth et al, 2009) Hearing impairment and working memory capacity WMC has been found to play the important role of supporting speech recognition in noise in individuals with HI (Akeroyd, 2008;Besser, Koelewijn, Zekveld, Kramer, & Festen, 2013;Gatehouse, Naylor, & Elberling, 2006;Lunner, 2003;Lunner & Sundewall-Thorén, 2007;Rudner et al, 2011). This has been shown for speech recognition of lowredundancy sentences material in background noise that is modulated, unmodulated (Lunner, 2003;Rudner, Foo, Rönnberg, & Lunner, 2009;Rudner et al, 2011) or modulated using competing speech (Desjardins & Doherty, 2013). In particular, WMC has been related to better speech recognition with different types of signal processing algorithms (Arehart et al, 2013;Gatehouse et al, 2006;Rudner, Foo, Rönnberg, et al, 2009;Rudner et al, 2011).…”
Section: Working Memory Capacitymentioning
confidence: 99%
See 2 more Smart Citations